Leptospirosis Cases among Outpatients with Non-Malaria Fever Attending Primary Care Clinics during the Rainy Season in Bobo Dioulasso, Burkina Faso - Zida, Sylvie; Kania, Dramane; Bolloré, Karine; Bandaogo, Ousséni; Pisoni, Amandine; Dicko, Amadou; Tinto, Bachirou; Traoré, Jacques; Van de Perre, Philippe; Ouédraogo, Henri Gautier; Tuaillon, Edouard (The American journal of tropical medicine and hygiene, 2024)
Leptospirosis is presumably an important cause of non-malarial fever in West Africa. In this study, outpatients consulting in primary care clinics during the rainy season were tested for leptospirosis, and clinical characteristics associated with leptospirosis cases were explored. Patients with fever ≥ 39°C were recruited in nine primary health care centers in Bobo Dioulasso (Burkina Faso). Diagnosis of malaria was ruled out using a rapid diagnostic test (RDT; SD Bioline Malaria ® ). Leptospirosis cases were defined as patients who tested positive for Leptospira IgM (Leptocheck-WB RDT and Leptospira IgM ELISA assay, Panbio) or DNA in plasma (LipL32 polymerase chain reaction [PCR]). Among 350 patients, 202 tested positive for malaria and were excluded, and 148 met the eligibility criteria and were included. Among these, 26 subjects were considered to be leptospirosis cases: 23 tested positive for Leptospira IgM (15.5%) and three tested positive by PCR (2.2%). Headaches, abdominal symptoms, and myalgia were frequently reported without any difference between leptospirosis cases and negative cases. Cough was more frequently observed among subjects testing positive for leptospirosis ( P = 0.02). Water exposure, presence of a skin injury, and walking barefoot were associated with a Leptospira -positive test. All leptospirosis cases recovered without sequelae. A significant portion of outpatients with non-malarial febrile illness during the rainy season in Burkina Faso had epidemiological factors associated with leptospirosis and tested positive for Leptospira . The favorable outcome of leptospirosis cases was reassuring; this could be due in particular to the young age of the patients.